Optimization of process conditions for citric acid production utilizing STP sludge as substrate by liquid state bioconversion - Alam, Md. Zahangir; Jamal, Parveen; Saari, Rosnani (2006)
Citric acid was produced by Aspergillus niger A-SS106 isolated from local sources utilizing sewage treatment plant (STP) sludge as substrate in laboratory scale process. Central composite design (CCD) was carried out to identify the total experiments for optimization of process conditions for citric acid production. The variables involved in the study were temperature, agitation rate, initial pH and inoculum size. A polynomial model was developed using the experimental data for determining the optimum process conditions through response surface methodology with respect to citric acid production. Statistical analysis of results showed the optimized values were: temperature of 30 ºC, agitation rate of 350 rpm, initial pH of 4 and inoculum size of 2%. Under the optimum conditions obtained from model equation, the predicted citric acid was 1.51 g/l produced on day 4. The maximum citric acid was 2.9 g/l obtained on day 2 under the optimum conditions.